Pengembangan Marketplace Maemma sebagai Upaya Peningkatan Pemasaran Usaha Makanan Bayi dan Anak - Pradana, Andika Kurnia Adi; Nurfarida, Ellya (Teknik Informatika Politeknik Kediri, 2017)
E-Marketplace is the one of ecommerce model that growth rapidly now. The concept of marketplace almost the same as other ecommerce, but there are any differences. E-marketplace can be consist of one provider that called admin or many provider that called seller. Now, we can access many e-marketplace such as tokopedia, olx, bukalapak and lazada. The e-marketplace businessâs are not selling specific product. They sell  alot of products. On the other hand, the business that run by UMKM can not develop as fast as the existing e-marketplaces. This also happen to the UMKM that sell babyâs foods and needs.  Whereas the food they sell contain balanced nutrition and do not contain subtances that harmfull to the baby. Maemma.id is the e-marketplace that built to provide babbyâs need especially UMKM food products and needs in Kediri Area. Maemma.id built using CodeIgniter framework, bootstrap and MySql database provide catalog product from each UMKM. The result of the research is e-marketplace website with  maemma.id domain. Maemma.id has access right for admin, seller and visitors. Admin serve to manage the seller data, seller manage the baby food products and needs they offer and visitors can see the good offered by certain categories and see the shop owner.